MODEL PEMBELAJARAN SENTRA MODEL PEMBELAJARAN PADA BASIS SENTRA DALAM PENGEMBANGAN KEMAMPUAN BERBAHASA ANAK USIA DINI DI KB DAN TK ISLAMIC CENTER SAMARINDA - Hidayah, Lailatul (Universitas Nahdlatul Ulama Kalimantan Timur, 2023)
The purposes of this research were to describe the design of learning models on a central base in developing expressive language skills, describe the implementation of the learning model on a center base in developing expressive language skills, describe the development of early childhood expressive language skills in KB and Kindergarten Islamic Center Samarinda. The research method used a qualitative approach, and the type of research used a case study. The research respondents were educators and students. The data were collected by interview, observation, and documentation. The data collected was then analyzed by reduction, presentation, and verification. Checking the trustworthiness of the data in this study was carried out by testing the validity of the data. Extending participation, triangulation, and peer discussion was pursued to obtain guaranteed credibility data while confirming ability was done with research results associated with the research process, triangulation, and data sources. The research results showed that learning design on a central base, implementation of learning models on a central base, and development of children's expressive language skills had significantly changed, and an improvement in expressive language skills.